(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores the critical role of Recognition, Validation, and Accreditation (RVA) in shaping educational systems globally. It examines how RVA ensures quality, credibility, and accessibility in education by analyzing its theoretical foundations, practical applications, and impacts. Through a literature review, methodological framework, and empirical insights, the article highlights RVA’s significance in fostering lifelong learning, equity, and institutional trust. The discussion offers recommendations for policymakers and educators to strengthen RVA frameworks.